1995
DOI: 10.1007/bf02208677
|View full text |Cite
|
Sign up to set email alerts
|

Nizatidine accelerates gastric emptying of a solid meal in rats

Abstract: Nizatidine, a new histamine-2-receptor antagonist, stimulates gastrointestinal motility in dogs and gastric emptying of liquids in rats. Effect of nizatidine on gastric emptying of a solid meal was investigated using a novel gastric emptying model in rats. Male Wistar rats (weighing 200-300 g) were supplied with powdered food containing 30 w/w% barium 14 hr before the beginning of the experiment and x-ray photography of rat stomach was taken under light ether anesthesia. Gastric emptying was assessed by percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…A number of studies (Robert et al, 1991;Matsuda et al, 1993;Burton-Freeman et al, 1997;Izbeki et al, 2001;Overhaus et al, 2004;Turan and Ozdemir, 2004) have exploited the intrinsic similarities between gastrointestinal metabolism of food in rats and hu-mans. Rats may be an effective model for gluten digestion because they are able to eat and digest a significant level of food (on the order of several grams, which would represent a physiological gluten load for a Celiac patient) in a suitable time frame (i.e., in approximately 5-8 h) (Kaneko et al, 1995).…”
mentioning
confidence: 99%
“…A number of studies (Robert et al, 1991;Matsuda et al, 1993;Burton-Freeman et al, 1997;Izbeki et al, 2001;Overhaus et al, 2004;Turan and Ozdemir, 2004) have exploited the intrinsic similarities between gastrointestinal metabolism of food in rats and hu-mans. Rats may be an effective model for gluten digestion because they are able to eat and digest a significant level of food (on the order of several grams, which would represent a physiological gluten load for a Celiac patient) in a suitable time frame (i.e., in approximately 5-8 h) (Kaneko et al, 1995).…”
mentioning
confidence: 99%
“…NZT is a selective histamine H2‐receptor antagonist, originally manufactured as a drug to treat peptic ulcer . However, in contrast to other H2‐receptor antagonists (cimetidine, famotidine, or ranitidine, famotidine) that lack prokinetic properties, NZT has a clear prokinetic effect on the gut in experimental animals and in humans . Therefore, while inhibiting gastric acid secretion via H2‐receptor antagonism, NZT promotes gastric motility .…”
Section: Discussionmentioning
confidence: 99%
“…Nizatidine enhances the gastric emptying of liquids in patients with gastric or duodenal ulcer, as measured by acetaminophen method [18]. Kaneko et al [35] have also reported that nizatidine, but not cimetidine or famotidine, dose-dependently accelerated gastric emptying of barium-containing solid meal in rats. In contrast, Koskenpato et al [36] have reported that nizatidine decreases the gastric emptying rate of solids without having a significant effect on symptoms or quality of life in FD patients.…”
Section: Discussionmentioning
confidence: 99%